Creativity from behind bars : A study of selected prison plays and films - Wafa{u2019} Abdallah Eid Saber; Amal Aly Mazhar (Cairo : Wafa{u2019} Abdallah Eid Saber, 2019)
This thesis aims to investigate different forms and representations of power relations, resistance, themes of hope and survival manifested in different dramatic plays and films written and produced about the experience of imprisonment. This will be done by closely examining the history of prison literature since the establishment of the modern prison around the 18th century, specifically by focusing most attention on Western and Arab works produced since the 1960s onwards. This will be accomplished by studying the significance of prison and its effect on inmates through examining their experience as portrayed in various media of expression, primarily plays and films.The thesis will apply cultural studies to the selected works through comparative Arab/West angles, as well as textual analysis. To achieve this, the study will rely on Michel Foucault's ideas and views on prison, compiled in his books Discipline and Punish: The Birth of the Prison and Power/Knowledge: Selected Interviews and Other Writings 1972-1977 where he discusses the roots and development of the penal system, the concepts of the Panopticon, surveillance, power relations, and the gaze to better understand the background of the modern prison system and the psychological and power dynamics in the selected works. The study also makes use of Martin Esslin's views on the importance of the signs on stage discussed in his book The Field of Drama: How the Signs of Drama Create Meaning on Stage and Screen. The selected works of incarceration were chosen to reflect different kinds of imprisonment: prisoners of war, hostages, criminal inmates, and psychological imprisonment. They are: Victoria Brittain and Gillian Slovo's verbatim play Guantanamo: {u2018}Honor Bound to Defend Freedom{u2019} (2005), Frank McGuinness's Someone Who'll Watch over Me (1992), and Abdel-Aziz Hammouda's al-Raha{u2019}en [The Hostages] (1982)
Thesis (M.A.) - Cairo University - Faculty of Arts - Department of English
Issued also as CD
Keywords: Behind bars; Prison literature; Prison plays and films